Antimicrobial properties and bonding durability of pH-responsive dentin adhesives with chlorhexidine-load mesoporous silica nanoparticles - Li, Sining; Qi, Le; Liu, Zhihui (Frontiers in Materials, 2024)
In this study, we synthesized pH-sensitive CHX@SBA-PDA nanoparticles and characterized their structure. These nanoparticles were then incorporated into Single Bond 2 commercial dentin adhesive. Subsequently, timely and long-term antibacterial evaluation, cytotoxicity evaluation and bonding properties were conducted. The results demonstrated the successful synthesis of CHX@SBA-PDA nanoparticles. Moreover, CHX@SBA-PDA exhibited excellent pH sensitivity and maintained a high release rate of chlorhexidine (CHX) under cariogenic low pH conditions. At pH 5.0, the release rate could reach up to 71.1% after 24 h of incubation with CHX@SBA-PDA nanoparticles. Among the different adhesive formulations tested, the 2% wt adhesive displayed the strongest immediate and 30 d bacterial inhibition ability (p < 0.05). No significant difference was observed in immediate shear strength among the four groups (p > 0.05). After undergoing pH cycling, all functional adhesive groups exhibited higher shear strength compared to the control group (p < 0.05). Furthermore, there was no significant difference in cell proliferation activity between the experimental group and control group (p > 0.05). In conclusion, our functional dentin adhesive containing CHX@SBA-PDA nanoparticles demonstrated long-term antibacterial properties as well as improved bond strength characteristics, thus, offering a promising approach to enhance durability of bonded restorations.